2003
DOI: 10.1117/12.478157
|View full text |Cite
|
Sign up to set email alerts
|

Flow regimes and mass transfer characteristics in static micromixers

Abstract: The design and calculation of micro mixers is done by conventional analytical and numerical calculations. Due to the small dimensions, laminar flow is expected and the mass transfer is supposed to be dominated by diffusion. A detailed CFD-study by CFDRC-ACE+ of simple static mixers shows a deviation from strictly laminar flow in a wide range of Re numbers and channel dimensions. The static mixers under test have a T-Profile with rectangular cross sections and characteristic dimensions of 50 to 400 µm. The mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 10 publications
2
28
2
Order By: Relevance
“…Using laminar flow the results of former studies on liquid flow [4,11,12] can be confirmed to hold true for gas phase flows. The simulations are based on a three-dimensional T-shaped micro channel geometry for the numerical grid.…”
Section: Fluid Dynamics Simulation Of the Micro-mixersupporting
confidence: 62%
See 1 more Smart Citation
“…Using laminar flow the results of former studies on liquid flow [4,11,12] can be confirmed to hold true for gas phase flows. The simulations are based on a three-dimensional T-shaped micro channel geometry for the numerical grid.…”
Section: Fluid Dynamics Simulation Of the Micro-mixersupporting
confidence: 62%
“…To prevent these particle losses, a redesign of the fluid inlet is necessary to avoid such bends and to allow a smooth, co-axial entrance into the mixer. Unfortunately, losses occur also in the mixing region, as seen in figure 8, most likely caused by the formation of vortices in the mixing zone [4], which prevents inertial particles from following the streamlines of these vortices and impacts them on the surrounding walls. The exit of the mixed flow region also shows visual signs of some particle deposition, which is, however, minor compared to the deposits found at the inlet and in the mixing zone.…”
Section: Resultsmentioning
confidence: 99%
“…Flow regimes in a T-mixer with a rectangular cross section are reported in the numerical study by Kockmann et al (2003). As they increased the Reynolds number, they observed laminar flow, then vortical flow, and then engulfment flow, in which the streamlines in the mixing channel are asymmetric.…”
Section: Introductionmentioning
confidence: 93%
“…Numerous studies [42][43][44][45][46] have shown that fast mixing (in the range of few milliseconds) can be achieved in T-mixers. Indeed, at Reynolds numbers (Re) greater than 400, vortices are created at the T-junction which enhances mixing.…”
Section: Mixing and Flow Propertiesmentioning
confidence: 99%